Metastatic uterine tumor resembling ovarian sex cord tumor: A case report and review of the literature - Michelle L. Kuznicki; Sharon E. Robertson; Ardeshir Hakam; Mian M. Shahzad (Elsevier, 2017)
Uterine tumors resembling ovarian sex cord tumors (UTROSCTs) are rare and commonly characterized as benign tumors, with infrequent reports of metastasis and recurrence. Treatment recommendations have not been well established, particularly for more advanced cases. We present the first reported death from a metastatic UTROSCT, summarize the available literature, and describe characteristics common to UTROSCTs with aggressive features. In this case, a 49-year-old woman presented with abdominal distension and pain; initial imaging and diagnostic workup suggested metastatic epithelial ovarian cancer to be the cause. The patient subsequently underwent neoadjuvant chemotherapy followed by optimal cytoreductive surgery and adjuvant chemotherapy. Final pathology revealed UTROSCT with omental and peritoneal metastases. She then underwent adjuvant chemotherapy with subsequent recurrence and died 15 months after her initial diagnosis. Our analysis of this case and the available literature led us to identify pathologic risk factors that may help predict aggressive UTROSCT behavior.